Avian biodiversity parameters in rice fields in Kuala Selangor, Malaysia - Mohd Hanafi, Nur Amira (2018)
Rice is one of the main staple food for most of Southeast Asian countries and it is one of the traditional crops in Malaysia and its neighbouring countries. Not only that, rice fields are common agricultural landscape of Southeast Asia that inhabited by various species of birds. This is because flooded rice fields provide similar environmental conditions to certain natural wetland habitats in terms of flooding condition, water depth and landscape features. Declination of wetland areas also one of the reasons birds are attracted to rice fields. These birds would provide ecosystem services that improve agricultural yields with minimum use of agrochemicals such as pesticides. Until now, there are quite a number of scientific studies that have investigated the status and ecology of birds in the rice fields of Malaysia. Thus, this study is the first to quantify avian biodiversity in rice production landscapes during three farming stages in Peninsular Malaysia. More specific, it determined bird abundance, species richness, and composition in rice field landscapes, and compared these during different stages of rice growing. This study was conducted at the rice fields in Kuala Selangor district. A total of 60 sampling points were randomly established in three locations, from which 3,447 individual birds of 46 species and 26 families were recorded. Water and land birds were counted in rice fields using the point-count method. There was a significant difference in bird abundance between the three different stages of rice growing. In bird species richness, the results showed significant difference during the various stages of rice growing.The growing stage supported greater bird abundance and more diverse species composition compared to the pre-harvest and post-harvest stages. Rice-growing provides temporary habitats to different bird species in the managed aquatic landscape. This implies the presence of abundant food, such as small fish and amphibians. In conclusion, the evidence from this study suggests that biodiversity friendly agricultural practices should be implemented to improve habitat quality for birds in rice production landscapes. Apart from being agricultural landscapes, rice fields also can be managed more as an off-reserve strategy in order to protect the waterbird diversity.